Actor Relations in the Pentahelix Model in Tourism Village Management: An Analysis of the Role of Government, Community, Private, Academic, and Media - Nurisma Rizky Nur Jannah; M. Husni Tamrin (Journal of Social and Policy Issues, 2026)
Tourism village management requires collaboration among multiple stakeholders to support destination sustainability and competitiveness. This study aims to analyze the management of Wringinanom Tourism Village using the Pentahelix approach by examining the roles and collaborative dynamics of the actors involved. The research employed a descriptive qualitative method. Data were collected through interviews, observations, and documentation, while informants were selected using purposive and snowball sampling techniques. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings reveal that the management of Wringinanom Tourism Village involves five Pentahelix actors. The community, represented by the Tourism Awareness Group (Pokdarwis), serves as the primary managing actor responsible for coordinating tourism activities, local SMEs, and homestay providers. The government plays a facilitative role through capacity building and administrative support, although tourism village management has not yet been strengthened by a specific Village Regulation. The private sector contributes to destination digitalization and marketing, academics support mentoring and innovation based on local potential, and the media function as promoters in expanding information dissemination and strengthening the destination image. The study concludes that the sustainability of Wringinanom Tourism Village depends on strengthening collaboration among Pentahelix actors, particularly through continuous innovation in tourism products and visitor experiences.